2018
DOI: 10.1186/s41702-017-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bacterial carriage on the hands of primary school children in Calabar municipality, Nigeria

Abstract: Background: Hand washing with soap and water is a good hand hygiene practice which reduces the chance of infection transmission through hand contact. This study was designed to determine the microbial hand carriage among nursery and primary school children in Calabar Metropolis and to assess the effect of hand washing in the reduction of bacterial hand carriage among these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
2
3
2
Order By: Relevance
“…coli (21.5%) respectively. This result coincided with the results reported in previous studies [ 7 , 8 , 10 , 14 , 31 , 32 , 34 , 39 ]. The isolation of Staphylococcus aureus could be because it is pathogenic bacteria that are normal flora of the skin and other body parts whereas the isolation of E .…”
Section: Discussionsupporting
confidence: 93%
“…coli (21.5%) respectively. This result coincided with the results reported in previous studies [ 7 , 8 , 10 , 14 , 31 , 32 , 34 , 39 ]. The isolation of Staphylococcus aureus could be because it is pathogenic bacteria that are normal flora of the skin and other body parts whereas the isolation of E .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the isolation rate of E. coli was 21.3%, which is comparable with a study conducted in India (20.68%) ( 5 ). The result is lower than the study performed in Iran (29.2%) ( 51 ), Nigeria (25.0%) ( 58 ), and Jimma University Specialized Hospital (JUSH) (25.4%) ( 20 ). However, the result is higher compared to previous studies conducted in Mauritius (0.5%) ( 26 ), in the ICUs of United States medical centers (7.1%) ( 57 ), and in the different parts of Ethiopia: Jimma University (10.9%) ( 15 ), Gondar Town (3.1 and 1.9%) ( 1 , 61 ), Debre Markos (2.7%) ( 17 ), UoGRH (5.9%) ( 13 ), University of Gondar (2.67%) ( 14 ), DMCSH (3.9%) ( 19 ), and Addis Ababa Regional Laboratory (3.6%) ( 60 ).…”
Section: Discussioncontrasting
confidence: 60%
“…e highest ratio value is for LX (5), whereas the least ratio value is for LFBY (1). e concave curve of (κ o /κ CMC ) with soaps is observed ( Figure 2).…”
Section: Conductivity and Ermodynamic Propertiesmentioning
confidence: 89%
“…ere have been many outbreaks of foodborne diseases and nosocomial infections due to hand contamination. Ogba et al [1] reported S. aureus followed by E. coli to be the most common isolates on the hands of primary school children in Nigeria. S. aureus and E. coli are associated with skin infections and food poisoning, respectively [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation